(untitled) (Fiep Bulletin - online, 2011)
The study proposes to address the perception of a particular group of parents of schoolchildren on school physical education and formation of the individual, leading to a reflection on the identity of physical education in schools. Used as a tool semi-structured questionnaire with twelve questions. The data were compared by using descriptive statistics, qualitative analysis with analysis and interpretation of results, where 44% of parents stated that the discipline of physical education has greater importance than the others and that 80% of parents believe that teacher education physics of their children be prepared to educate and mold children as future citizens. At the end of the study, there has been a concern of parents in the education of its children as a citizen and fully, not only a physical perspective as before and also stood out as the credit capacity of the physical education teacher needs to suppress students and an increased emphasis by parents regarding the cognitive and socio-affective.